2014
DOI: 10.1042/bj20131014
|View full text |Cite
|
Sign up to set email alerts
|

Ser119 phosphorylation modulates the activity and conformation of PRRXL1, a homeodomain transcription factor

Abstract: PRRXL1 [paired related homeobox-like 1; also known as DRG11 (dorsal root ganglia 11)] is a paired-like homeodomain transcription factor expressed in DRG and dSC (dorsal spinal cord) nociceptive neurons. PRRXL1 is crucial for the establishment and maintenance of nociceptive circuitry, as Prrxl1(-/-) mice present neuronal loss, reduced pain sensitivity and failure to thrive. In the present study, we show that PRRXL1 is highly phosphorylated in vivo, and that its multiple band pattern on electrophoretic analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…2B), with Prrxl1 displaying the strongest effect. Accordingly, recent data showed that Prrxl1 has a repressor domain spanning amino acids 227-263 of Prrxl1, which is not present in Prrxl1b [28]. No repression was detected when using a region spanning Prrxl1 alternative promoters downstream of the TATA box [À604/À50].…”
Section: Prrxl1 Acts As a Repressor Of Its Own Transcriptionmentioning
confidence: 99%
“…2B), with Prrxl1 displaying the strongest effect. Accordingly, recent data showed that Prrxl1 has a repressor domain spanning amino acids 227-263 of Prrxl1, which is not present in Prrxl1b [28]. No repression was detected when using a region spanning Prrxl1 alternative promoters downstream of the TATA box [À604/À50].…”
Section: Prrxl1 Acts As a Repressor Of Its Own Transcriptionmentioning
confidence: 99%
“…Recently, we have shown that Prrxl1 is differentially phosphorylated in the dorsal spinal cord and DRG along development [19]. The increase in phosphorylation state is accompanied by conformational changes resulting in a multiple band pattern on electrophoretic analysis [19].…”
Section: Tlx3 Induces Prrxl1 Hyperphosphorylationmentioning
confidence: 99%
“…To better understand the regulatory mechanisms implicated in Tlx3 and Brn3a control of Prrxl1 expression, we performed gain-and loss-offunction experiments in ND7/23 cells, a DRG-derived cell line previously shown to be a suitable model for studying Prrxl1 [9,19]. Given that promoters P1 and P2 share many features, we decided to analyse these DNA regions as a single module.…”
Section: Tlx3 and Prrxl1 Synergistically Act To Activate Prrxl1 Promomentioning
confidence: 99%
See 2 more Smart Citations